2015
DOI: 10.1515/hf-2014-0264
|View full text |Cite
|
Sign up to set email alerts
|

Modification of acid hydrolysis lignin for value-added applications by micronization followed by hydrothermal alkaline treatment

Abstract: Technical hydrolysis lignin (THL) was micronized by grinding in a rotary-jet mill to obtain a fraction of approximately 5 mm. Both initial and milled THLs were liquefied by thermal alkaline treatment at 220°C for 2 h. Upgraded THLs that were nonmilled (L1) and milled (L2) were desalted by treatment with cation-exchanged resin and were dried. Micronization affected the course of hydrothermal alkaline treatment and the structure and composition of the obtained lignin. Thus, L2 contained much less concomitant pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The molecular weight was ≈1000 Da, as determined by size-exclusion chromatography. Structural characterization carried out by employing tandem electrospray ionization-mass spectrometry and 1D and 2D nuclear magnetic resonance spectroscopy revealed that upgraded lignins are oligomers (trimerspentamers) with highly degraded propane chains and possess polyconjugated condensed aromatic structures [27,28].…”
Section: Preparation Of Filmsmentioning
confidence: 99%
“…The molecular weight was ≈1000 Da, as determined by size-exclusion chromatography. Structural characterization carried out by employing tandem electrospray ionization-mass spectrometry and 1D and 2D nuclear magnetic resonance spectroscopy revealed that upgraded lignins are oligomers (trimerspentamers) with highly degraded propane chains and possess polyconjugated condensed aromatic structures [27,28].…”
Section: Preparation Of Filmsmentioning
confidence: 99%
“…The majority of the mass spectra were obtained in the m/z range up to m/z 1000 19–23,26,37 or m/z 1500, 19,24,28,38,39 often with the main goal being to evaluate lignin degradation products 40–42 . However, the MW was mostly left undetermined, 19–24,26,28,37–39 although some studies mentioned the mass range in Daltons in addition to the m/z range, thus recognizing the formation of multiply charged species typical for ESI 15,24,27 . The mass range reported after a presumed deconvolution reached up to 2400, 4500 and 7000 Da 15,24,28 .…”
Section: Esi‐ms Analysis Of Ligninmentioning
confidence: 99%
“…Extensive studies have been performed on the Physico-chemical modification of alkali lignin structure to increase its water solubility [10][11][12]. The chemical modification of lignin can be achieved by different approaches include reaction with epichlorohydrin, formaldehyde, phenol, propylene carbonate, polyethylene glycol [13][14][15]. Moreover, The modified lignin can be obtained by introducing cationic or anionic moieties to increase its solubility [16].…”
Section: Introductionmentioning
confidence: 99%